2009
DOI: 10.4141/cjps08051
|View full text |Cite
|
Sign up to set email alerts
|

Control of common waterhemp (Amaranthus tuberculatus var. rudis) in corn and soybean with sequential herbicide applications

Abstract: Soltani, N., Vyn, J. D. and Sikkema, P. H. 2009. Control of common waterhemp (Amaranthus tuberculatus var. rudis) in corn and soybean with sequential herbicide applications. Can. J. Plant Sci. 89: 127Á132. Common waterhemp (Amaranthus tuberculatus) is an aggressive annual broadleaf whose distribution is expected to increase rapidly in agricultural land in eastern Canada. Eight field experiments (four in corn and four in soybean) over a 2-yr period (2005 and 2006) were established on two Ontario farms (near Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Ganie et al (2017) observed 2% to 4% corn injury at 7 DAPRE with saflufenacil plus dimethenamid-P at a rate higher (780 g ha −1 ) than that applied in this study (390 g ha −1 ). Some studies also reported minimal to no corn injury with dicamba (600 g ha −1 ), dicamba plus diflufenzopyr (200 g ha −1 ), or dicamba plus halosulfuron (380 g ha −1 ) at 14 DAPOST (Ganie et al 2017; Kohrt and Sprague 2017; Soltani et al 2008). VanGessel et al (2016) reported hybrid corn stunting and leaf chlorosis up to 10% at 7 DAPOST application of dicamba plus diflufenzopyr at twice (588 g ha −1 ) the labeled rate.…”
Section: Resultsmentioning
confidence: 99%
“…Ganie et al (2017) observed 2% to 4% corn injury at 7 DAPRE with saflufenacil plus dimethenamid-P at a rate higher (780 g ha −1 ) than that applied in this study (390 g ha −1 ). Some studies also reported minimal to no corn injury with dicamba (600 g ha −1 ), dicamba plus diflufenzopyr (200 g ha −1 ), or dicamba plus halosulfuron (380 g ha −1 ) at 14 DAPOST (Ganie et al 2017; Kohrt and Sprague 2017; Soltani et al 2008). VanGessel et al (2016) reported hybrid corn stunting and leaf chlorosis up to 10% at 7 DAPOST application of dicamba plus diflufenzopyr at twice (588 g ha −1 ) the labeled rate.…”
Section: Resultsmentioning
confidence: 99%
“…When left uncontrolled, waterhemp can reduce corn yield up to 74% [18]. In Ontario, corn yield loss up to 48% has been reported [19]. Corn should be kept weed-free from emergence (VE) to the V6 corn stage to prevent yield loss caused by waterhemp interference [18].…”
Section: Introductionmentioning
confidence: 99%
“…Waterhemp left uncontrolled can reduce grain corn yield by up to 74% (Steckel & Sprague, 2004). In Ontario, corn yield losses of up to 48% have been reported when MHR waterhemp population resistant to Group 2 and 5 herbicides were left uncontrolled (Soltani et al, 2009). HPPD-inhibiting herbicides are widely used in corn production due to their crop safety, flexible application timing, broad spectrum weed control and activity on many HR weed species.…”
Section: Introductionmentioning
confidence: 99%